PEMANFAATAN FASILITAS BELAJAR DI SEKOLAH DAN PENGARUHNYA TERHADAP HASIL BELAJAR IPS SISWA KELAS VIII MTs DARUL FALAH CERMEE BONDOWOSO SEMESTER GENAP - Nursalam Nursalam (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2014)
The learning process and its results are influenced by several factors, including learning facilities. Learning facilities was including all of the necessary equipment in the learning process so that the learning objectives can be achieved smoothly, orderly, effective, efficient, and students can achieve optimal learning outcome. This research is a quantitative research with ex post facto research design. The study population was all students of class VIII MTs Darul Falah Cermee Bondowoso as many as 183 students. From that population, the sample was determined by using random sampling methods as many as 70 students. Data collection techniques which used in this research was questionnaire and documentation. After analyzing with simple regression analysis techniques, the results showed that the value of F regression is 409.304 with significance level 0.000% and the F table shows the value of 3.98 on a = 0.05 and 7.02 on a = 0.01. Based on these results, the value of F regression is more than the F table value, either on a = 0.05 and a = 0.01, it can be concluded that the independent variables (predictors) have a significant effect on the dependent variable (criterion). In addition, the effectiveness of the regression line shows the percentage of 85.75%. Thus, the use of school facilities have a significant effect as many as 85,75% on student’s science learning outcomes on eighth grade MTs Darul Falah Cermee Bondowoso on the second semester.